1996
DOI: 10.1021/jp9516093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orientation of Porphyrin Single-Crystal Slices on Optoelectronic Properties

Abstract: Millimeter-sized organic single-crystal slices of methylpyrroporphyrin XXI ethyl ester (MPPEE) have been prepared by capillary filling at its melting point (∼250°C) between two parallel pieces of glass coated with indium-tin oxide (ITO) and separated by about 2-3 µm. Crystal orientation was characterized with polarized light under an optical microscope. MPPEE single-crystal slices with different orientations appeared as dramatically different colors between two crossed polarizers. The relationship between crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 19 publications
5
34
0
Order By: Relevance
“…The orientation of these bulky groups insulates the core and prevent aggregation of the dye thereby improving the V oc . Also it is known that the surface orientation of the dye strongly impacts the optoelectronic properties by altering the effective barrier width for through space charge tunneling and the μ orientation which influences the electron injection . It is also observed in our study that, all the dyes bearing alkoxy chains at ortho ‐positions of their meso ‐phenyl rings have R2 and R4 groups oriented perpendicular to the plane of porphyrin ring.…”
Section: Resultssupporting
confidence: 64%
“…The orientation of these bulky groups insulates the core and prevent aggregation of the dye thereby improving the V oc . Also it is known that the surface orientation of the dye strongly impacts the optoelectronic properties by altering the effective barrier width for through space charge tunneling and the μ orientation which influences the electron injection . It is also observed in our study that, all the dyes bearing alkoxy chains at ortho ‐positions of their meso ‐phenyl rings have R2 and R4 groups oriented perpendicular to the plane of porphyrin ring.…”
Section: Resultssupporting
confidence: 64%
“…[9,16±21] In a number of previous works it has been shown that a clear relationship exists between the mobility of charge carriers and the thermotropic phase of the liquid-crystalline porphyrin layer. [15,19,22] Also, the quasi-one-dimensional character of the charge transport within these stacks has been demonstrated. [19] However, so far only a few studies concerning the relationship between the molecular arrangement within a porphyrin antenna layer and the exciton diffusion length have been reported.…”
Section: Introductionmentioning
confidence: 94%
“…[15,19,22] Also, the quasi-one-dimensional character of the charge transport within these stacks has been demonstrated. [19] However, so far only a few studies concerning the relationship between the molecular arrangement within a porphyrin antenna layer and the exciton diffusion length have been reported. [15] Recently, we have shown that the flash-photolysis time-resolved microwave conductivity technique (FP-TRMC) provides a powerful method for measuring the dynamics of photoinduced CS in photoactive systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, electrons from the excited state of ZnODEP molecules are injected into the irradiated ITO contact ͑termed an anodic current͒ while positive charges move to the opposite electrode. 1,5,[7][8][9][10][11][12][13] The relation between I sc as a function of time without bias ͑the short-circuit photocurrent͒ from pixel 4D is shown in Fig. 2b.…”
mentioning
confidence: 99%